Aborsi Dalam Perspektif Kajian Hadis - Nurhaidi, Dadi (Musawa Jurnal Studi Gender dan Islam, 2003)
In this article Dadi shows that there are dozens of hadith concerning abortion, most of which are valid From the analysis of these it appeals that people who abort a foetus must pay a fine, which could be in the form of freeing a slave, paying with five camels or one hundred sheep or paying a cash equivalent to this price. Nevertheless, this article states that although in the hadith abortion is regarded as a crime, it is not considered murder because the foetus is not yet "separated" from its mother. As such the punishment for abortion is not the same as the punishment for murder.